2007
DOI: 10.1111/j.1445-5994.2007.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

How intravenous immunoglobulin is used in clinical practice: audits of two Sydney teaching hospitals

Abstract: These audits emphasize the requirement for updated National Clinical Practice Guidelines, improved approval procedures, consensus statements in the specialties of immunology, haematology and neurology and clarification of the role of drug committees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 3 publications
(7 reference statements)
2
34
1
Order By: Relevance
“…Contrary to their statements, our data from two Sydney teaching hospitals effectively challenge the perception that total IVIg use in Australia is accurately described by category 1 indications of the AHMAC 2000 guidelines 1 …”
Section: Replycontrasting
confidence: 98%
See 1 more Smart Citation
“…Contrary to their statements, our data from two Sydney teaching hospitals effectively challenge the perception that total IVIg use in Australia is accurately described by category 1 indications of the AHMAC 2000 guidelines 1 …”
Section: Replycontrasting
confidence: 98%
“…Our i.v. immunoglobulin (IVIg) audit findings led us to conclude that IVIg is approved and distributed by complex procedures that exist in the context of rapid changes in clinical practice 1 . Australian Red Cross Blood Service (ARCBS) representatives Dennington et al have confirmed these findings.…”
Section: Replymentioning
confidence: 98%
“…The IVIg have been used in different specialties, and two of them (internal medicine and neurology) have included 75.1% of the patients (79.0% of the total IVIg quantity). In this study, nearly the half of the IVIg have been used in internal medicine specialty, whereas this clinical specialty was little (5.6%) or not reported in other studies [1,6,10]. It may be explained by the fact that haematologic pathologies (as primary or secondary immune deficiency and PTI) are cared in internal medicine specialty in our hospitals, whereas they can be cared in other medical units in other countries.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, it was more often for unlabelled indications [7–9]. This increase in IVIg use is linked to different difficulties such as the lack of resource with the risk of shortage and its high cost [1,10,11]. This growth has conducted some countries to review the IVIg use and to publish guidelines [1,6,12–14].…”
Section: Introductionmentioning
confidence: 99%
“…Off label use of IVIG happens worldwide, an audit of IVIG use revealed a greater than expected proportion of non-category 1 IVIG use 9 . The ICU is a challenging setting as interventions may be life saving whereas the critically ill patients may be prone to develop complications.…”
Section: Discussionmentioning
confidence: 99%